(untitled) (Research Announcements "Heritage BG", 2025)
In this paper, I reconstruct a narrative by Tertullian about a dreaming Saturn attributed to a lost dialogue of Aristotle (on my view, the Eudemus). I argue that it is crucial to place this narrative into its proper geographical and cultural context, namely, Macedonia and Macedonian religion. Indeed, I show that Aristotle draws upon a myth in circulation in Macedonia which blended Greek Kronos with Thracian Zalmoxis. This is not surprising given that Aristotle spent not only his childood in Macedonia, but also ten years of his adulthood teaching in Mieza, in close proximity to Thracian tribes in Macedonia. References: Popov, Dimitar. (1995). Богът с много имена. Sofia: Sofia University St. Kliment Ohridski Press. Archibald, Zosia. (2010). Macedonia and Thrace. In: A Companion to Ancient Macedonia (eds. Joseph Roisman, Ian Worthington). Oxford: Blackwell, 326-41. Bos, Abraham P. (1989). A Dreaming Kronos in a Lost Work by Aristotle. – L’Antiquité Classique, Tome 58, 88-111. Bos, Abraham P. (2003). The Soul and Its Instrumental Body. A Reinterpretation of Aristotle’s Philosophy of Living Nature. Leiden and Boston: Brill. Brisson, Luc. (2000). L’incantation de Zalmoxis dans le Charmide (156d-157c). In: Plato: Euthydemus, Lysis, Charmides: Proceedings of the V Symposium Platonicum: Selected Papers (eds. Thomas M. Robinson, Luc Brisson). Berlin: Academia Verlag, 278-86. Brown, Malcolm Kenneth. (2002). The Narratives of Konon: Text, Translation and Commentary on the Diegeseis. Berlin: De Gruyter. Carpenter, Rhys. (1946). Folk Tale, Fiction, and Saga in the Homeric Epics. Berkeley and Los Angeles: University of California Press. Christensen, Paul, Sarah C. Murray. (2010). Macedonian Religion. In: A Companion to Ancient Macedonia (eds. Joseph Roisman, Ian Worthington). Oxford: Blackwell, 428-45. Chroust, Anton-Hermann. (1965). Aristotle and the Philosophies of the East. - The Review of Metaphysics, vol. 18, no. 3, 572-580. Chroust, Anton-Hermann. (1972). Aristotle and the Foreign Policy of Macedonia. – The Review of Politics, vol. 34, no. 3, 367-94. Dana, Dan. (2007). Zalmoxis et la quête de l’immortalité: pour la révision de quelques théories récentes. - Les Études Classiques, vol. 75, 93-110. Diogenes. (2013). Diogenes Laertius: Lives of Eminent Philosophers, ed. T. Dorandi. Cambridge: Cambridge University Press. Dodds, Eric R. (1951). The Greeks and the Irrational. Oakland: University of California Press. Düring, Ingemar. (1956). Aristotle and Plato in the Mid-Fourth Century. - Eranos. Acta Philologica Suecana, vol. 54, 109-120. Gaiser, Konrad. (1985). Ein Gespräch mit König Philip: Zum Eudemos. In: Aristoteles Werk und Wirkung: Paul Moraux Gewidmet 1. Band: Aristoteles und seine Schule (ed. Jürgen Wiesner). Berlin: De Gruyter, 457-484. Gigon, Olof. (1950). Aristotles: Vom Himmel, Von der Seele, Von der Dichtkunst. Eingeleitet und neu übertragen von Olof Gigon. Zürich: Artemis. Herodotus. (1890). The History of Herodotus, trans. G.C. Macaulay. London: Macmillan. Herodotus. (2015). Herodoti Historiae, 2 vols., ed. N.G. Wilson. Oxford: Oxford University Press. Hesychius Alexandrinus. (1953-1966). Hesychii Alexandrini lexicon, vols. 1-2, ed. K. Latte. Copenhagen: Munksgaard. King, Carol J. (2010). Macedonian Kingship and Other Political Institutions. In: A Companion to Ancient Macedonia (Eds. Joseph Roisman, Ian Worthington). Oxford: Blackwell, 371-391. McPherran, Mark L. (2004). Socrates and Zalmoxis on Drugs, Charms, and Purification. – Apeiron, vol. 37, no. 1, 11-33. Murphy, David J. (2000). Doctors of Zalmoxis and Immortality in the Charmides. In: Plato: Euthydemus, Lysis, Charmides: Proceedings of the V Symposium Platonicum: Selected Papers (eds. Thomas M. Robinson, Luc Brisson). Berlin: Academia Verlag, 287-95. Plato. (1903, repr. 1968). Platonis opera, vol. 3, ed. J. Burnet. Oxford: Clarendon Press. Plutarch. (1928, repr. 1962). Plutarch’s Moralia, vol. 2, ed. F. C. Babbitt. Cambridge, Mass.: Harvard University Press. Plutarch. (1960). Plutarch’s Moralia, vol. 5.3, trans. M. Pohlenz. Leipzig: Teubner. Popov, Dimitar. (2010). “Zalmoxis.” – In: Popov, Dimitar, Valeria Fol. The Deities of the Thracians. Sofia: ТАNGRA TanNakRaНГРА, 166-193. Porphyry. (1886, repr. 1963). Porphyrii philosophi Platonici opuscula selecta, 2nd edition, ed. A. Nauck. Leipzig: Teubner, repr. Hildesheim: Olms. Roller, Lynn E. (1983). The Legend of Midas. Classical Antiquity, vol. 2, no. 2, 299-313. Ross, William D. (1960). Works of Aristotle Vol. XII: Select Fragments. Oxford: Oxford University Press. Strabo. (1877). Strabonis Geographica, 3 vols., ed. A. Meineke. Leipzig: Teubner. Suidae Lexicon. (2001). Suidae Lexicon, 4 vols. Lexicographi Graeci 1.1-1.4, ed. A. Adler. Leipzig: Teubner. Tertullian. (1947). De anima: Edited with introduction and commentary by J.H. Waszink. Amsterdam: J.M. Meulenhoff. Tertullian. (1961). Apologeticum. Verteidigung des Christentums, trans. Carl Becker. München, Kösel. Vassileva, Maya. (1997). King Midas: Between the Balkans and Asia Minor. – Dialogues d’histoire ancienne, vol. 23, no. 2, 9-20. Waszink, Jan H. (1947). Traces of Aristotle’s Lost Dialogues in Tertullian. – Vigiliae christianae, vol. 1.3, 137-149.